Prevalence of Alveolar Antral Artery in Patients Visiting Tertiary Care Center: A Cone-beam Computed Tomography Study - Subedi , Gitanjali; Lamichhane, Simant; Rijal, Arjun Hari; Humagain, Manoj; Bhusal, Sita; Timilsina, Samina (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Introduction: Intra-osseous anastomosis between the posterior superior alveolar artery (PSA) and infraorbital artery is termed as Alveolar Antral Artery (AAA). It is considered a common anatomical point of interest during lateral sinus floor elevation because of the risk of intra-operative hemorrhage. Objective: To determine the prevalence of AAA along with its diameter and distance from the floor of the maxillary sinus. Methods: A total of 250 Cone-beam Computed Tomography (CBCT) images scanned with a Dentium Rainbow CBCT machine were included in the study. The study design was a descriptive cross-sectional study, done from archives of the Department of Oral Medicine and Radiology at Dhulikhel Hospital from June 2023 – October 2023. Using the multiplanar capabilities of the software, the prevalence, exact location, and diameter of the artery were determined in relation to the floor of the maxillary sinus. Data were collected and entered into Microsoft Excel and analysis was done in SPSS version 20.0. Results: The artery could be identified in 197 (78.8 %) of the cases on the right maxillary sinus and 185 (74 %) of the cases on the left maxillary sinus. The mean diameter of the artery on the right sinus was found to be 1.24 mm and 1.10 mm on the left. The mean distance from the floor of the sinus was 10.22 mm on the right and 8.52 mm on the left side. Conclusions: One significant anatomical feature in the wall of the lateral maxillary sinus is the alveolar antral artery. Preoperative CBCT scans are useful diagnostic tools for conditions that may affect this artery and for reducing surgical complications in suspected cases.